The contribution of higher-order thinking skills to the mathematics learning achievement of grade VIII students at SMP IT Al-Hijrah - Indriani Tutuarima; Edi Syahputra (Universitas Muhammadiyah Enrekang, 2025)
This research aims to determine the contribution of higher-order thinking skills to the mathematics learning achievement of eighth-grade students at SMP IT Al-Hijrah. The higher-order thinking skills analyzed include mathematical reasoning, problem-solving, analytical ability, critical thinking, and creative thinking. This research is based on the importance of developing higher-order thinking skills in the mathematics learning process to enhance students' ability to think deeply and apply their knowledge in problem-solving, as well as to improve students’ mathematics learning achievement in school.. The research method used a quantitative approach with an ex post facto design. The research population was all eighth-grade students in the 2024/2025 academic year, with a sample of 60 students taken from all eighth-grade classes. Data was collected through test instruments that had been tested for validity and reliability. Data analysis was performed using multiple linear regression to determine the contribution of each aspect of higher-order thinking skills to mathematics learning achievement. The results showed that mathematical reasoning skills contributed 22%, problem-solving 16%, analytical ability 19.6%, critical thinking 21.2%, and creative thinking 15.3% to mathematics learning achievement. The findings indicate that all components of higher-order thinking skills have a significant contribution to student learning achievement. The conclusion of the study is that there is a positive and significant relationship between higher-order thinking skills and the mathematics learning achievement of eighth-grade students at SMP IT Al-Hijrah. Based on the results of this study, it is recommended for teachers to more fully integrate the development of higher-order thinking skills in the mathematics learning process. Teachers can use teaching approaches that emphasize reasoning, problem-solving, analysis, critical thinking, and creative thinking, both through the use of contextual-based questions and innovative learning models that foster deep and applied thinking skills. Furthermore, schools are expected to provide ongoing training for teachers to enhance pedagogical competencies in implementing higher-order thinking skills-based learning, in order to optimally support the improvement of students' mathematics learning achievements